Outcome of Ultrasound-guided Autologous Platelet-rich Plasma Injection in Patients with Adhesive Capsulitis - Nahid Sultana; Nashid Sultana Ishi; Sadia Tasnim Munmun; Md Mizanur Rahman; Ariful Huda; Mohammad Shohidullah (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: Adhesive capsulitis (frozen shoulder) causes substantial pain and disability, and evidence for platelet-rich plasma (PRP) as a minimally invasive therapy in our setting remains limited. This study evaluated whether intra-articular autologous PRP, added to standard conservative care, improves pain and functional outcomes in adhesive capsulitis. Methods: An open-label randomized controlled trial was conducted in the Department of Physical Medicine & Rehabilitation, BMU, over 12 months. Sixty adults with adhesive capsulitis were randomized by lottery to: (i) PRP injection plus conservative management with a rehabilitation program, or (ii) conservative management with rehabilitation alone. Outcomes were assessed using the Visual Analogue Scale (VAS) for pain and the Shoulder Pain and Disability Index (SPADI) at baseline and follow-up intervals to six months. Data were analyzed in SPSS v23 with α=0.05. Results: At three months, VAS pain reduction and SPADI improvements were greater in the control group; however, by six months both pain and disability improved more in the PRP group than in controls. Adverse events occurred in 10.7% of the PRP group and 6.9% of controls, with no significant between-group difference. Diabetes mellitus and hypertension were the most frequent comorbidities, and diabetes prevalence was higher in the PRP arm. Age, sex, and BMI were not associated with outcome differences in either group. Conclusion: Intra-articular autologous PRP, as an adjunct to conservative management, yields superior pain and disability outcomes at six months compared with conservative care alone, with a comparable safety profile. These findings support PRP as a viable longer-term option for adhesive capsulitis within our context. J Shaheed Suhrawardy Med Coll 2024; 16(2): 24-29